Psychotherapeutic interventions in the treatment of depersonalisation-derealisation disorder - Pyliagina Галина; Kobzar Оксана (Psychosomatic Medicine and General Practice, 2025)
Introduction. Today, mental disorders manifested by depersonalisation and/or derealisation, as a sign of dissociative defence mechanisms, are one of the most common pathological phenomena, especially in adolescence and young adulthood. The article provides an overview and reasoning behind the choice of tools for short-term psychotherapeutic intervention in the treatment of depersonalization-derealization disorder (DDDs) based on clinical cases’ analysis of patients with this pathology. Objective. Investigate the effect of targeted psychotherapeutic intervention in the management of patients with DDDs. Materials and Methods. The analysis of patients’ clinical cases with DDDs is presented as examples of early and late (concern to the course of the disorder) targeted psychotherapeutic intervention in the curation of DDDs. Results. Based on the diagnostics of DDDs in patients using a semi-structured clinical interview and psychodiagnostics examination, a plan (protocol) for targeted psychotherapeutic intervention was developed and applied. It’s aimed to enhancement the effectiveness of treatment for patients with DDDs. Keywords: diagnostics and treatment of mental disorders, depersonalization, derealization, dissociation, depersonalization-derealization disorder, psychotherapeutic approaches to the treatment of mental disorders УДК: 616.89-008.42:616.89-008.428.1-053.7/.84-036.1-079.4-08